2008
DOI: 10.18618/rep.2008.4.251257
|View full text |Cite
|
Sign up to set email alerts
|

Metodologia De Eficiência Energética Aplicada Em Sistemas De Bombeamento

Abstract: Resumo-O objetivo deste trabalho é apresentar uma metodologia de comparação do desempenho de sistemas de bombeamento controlados por válvulas de estrangulamento e a utilização de inversores de freqüência no controle da vazão. Adicionalmente, identificar a redução do consumo de energia elétrica bem como justificativas da escolha de um sistema em detrimento do outro. Palavras-Chaveeficiência energética, inversor de freqüência, sistemas de bombeamento.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In cases in which the motor-pump set is oversized, as is the analyzed case, the slope does not affect the pumping costs when the drive is not used because excess pressure is dissipated in the form of pressure loss in the control valve, increasing the power that can be saved using the variable-frequency drive. Ferreira et al (2008) analyzed energy efficiency in pumping systems and found that the potential for electricity savings when using a variable-frequency drive instead of the dissipative method depends on the proximity of the project point to the motor-pump operation point. Figure 3 shows the total annual costs under the conditions with and without the variable-frequency drive, terrain slopes of 0, 5, and 10%, and annual irrigation time of 500, 1000, 1500, 2000 h. The total annual cost is higher when no variable-frequency drive is used, regardless of the annual irrigation time.…”
Section: Cmentioning
confidence: 99%
“…In cases in which the motor-pump set is oversized, as is the analyzed case, the slope does not affect the pumping costs when the drive is not used because excess pressure is dissipated in the form of pressure loss in the control valve, increasing the power that can be saved using the variable-frequency drive. Ferreira et al (2008) analyzed energy efficiency in pumping systems and found that the potential for electricity savings when using a variable-frequency drive instead of the dissipative method depends on the proximity of the project point to the motor-pump operation point. Figure 3 shows the total annual costs under the conditions with and without the variable-frequency drive, terrain slopes of 0, 5, and 10%, and annual irrigation time of 500, 1000, 1500, 2000 h. The total annual cost is higher when no variable-frequency drive is used, regardless of the annual irrigation time.…”
Section: Cmentioning
confidence: 99%